Gilles Deleuze : an introduction - May, Todd, 1955- (Cambridge University Press, 2005)
This book offers a readable and compelling introduction to the work of one of the twentieth century's most important and elusive thinkers. Todd May organizes his book around a central question at the heart of Deleuze's philosophy: how might we live?